Cytokines and chemokines in testicular inflammation: A brief review - Guazzone, Vanesa Anabella (2009)
A wide spectrum of data in the literature shows the relevance of cytokines as paracrine regulators of spermatogenesis and steroidogenesis in the normal testis. In this brief review, we highlight the relevance of cytokines in the testis during inflammation. This phenomenon involves complex and multiple interactions among immune and germ cells generally resulting in the alteration of spermatogenesis. The complexity of these cell interactions is multiplied because Sertoli and Leydig cells are also producers of pro- and anti-inflammatory cytokines and chemokines. Also, cytokines are pleiotropic and they exert opposite and/or redundant effects in different conditions. However, in spite of this bidirectional immunoregulatory function of cytokines, the mass of the data, reported from experiments of acute testicular inflammation, shows upregulation of interleukin (IL)-1beta, IL-1alpha, IL-6, and tumor necrosis factor alpha (TNF-alpha), which induce adverse effects on germ cells. In autoimmune orchitis, a chronic testicular inflammation, chemokines such as CCL2, CCL3, and CCL4 induce attraction and extravasation of immune cells within the testicular interstitium. These cells alter the normal immunosuppressor microenvironment principally through the secretion of proinflammatory cytokines, interferon-gamma initially, and IL-6 and TNF-alpha thereafter. Germ cells expressing TNFR1, IL-6R, and Fas increase in number and undergo apoptosis, through the TNF-alpha/TNFR1, IL-6/IL-6R, and Fas/Fas L systems. The knowledge of immune-germ and somatic testicular cell interactions will contribute to the understanding of the mechanisms by which chronic inflammatory conditions of the testis can disrupt the process of spermatogenesis.